„A trip organised for children is not a serious matter“? Summer treatment camps for the Belgian-German borderlands (1919–1939). - Venken, Machteld (Childhood, 2025)
„Although the children whose rural homelands transitioned from German to Belgian state sovereignty following the First World War were not the typical demographic targeted for preventive air treatments against tuberculosis, they were overrepresented in treatment camps in both Belgium and Germany. Nation-state representatives provided public and private (although partly state subsidized) treatment camps to restore the physical vitality, ethical integrity, and national allegiances of the minors. The parallel competitive offer took the form of a cross-border mixed economy of child welfare. Borderland residents either opportunistically supported the Belgian or German initiatives, or provided their own alternatives to protect their children from indoctrination.“
Keywords: Heilanstalt; Jugend; Kind; Nationalbewusstsein; Nationalismus; Nationenbildung; Verschickung

Borderland Child Heterotopias. A Case Study on the Belgian-German Borderlands - Venken, Machteld (Journal of Borderlands Studies, 2021)
Abstract: „This article investigates the capacities of children to participate actively in their lives in the Belgian-German borderlands in the time period between World War I and World War II. The article interprets a body of historical sources that has hitherto been left unexplored – namely, borderland child ego documents – with the help of insights from child studies and border studies. These ego documents unfold as borderland child heterotopias. Borderland child heterotopias include material places and creative linguistic loci established by or for those considered in crisis in relation to the rest of society based on their age within or outside child spaces of modernity. The borderland child heterotopias offer a unique gateway to borderland children’s past imaginations for a better world.“
Keywords: Grenzgebiet; Kind; Sozialraum